Antibody-Dependent Enhancement of SARS-CoV-2 Infection Is Mediated by the IgG Receptors FcγRIIA and FcγRIIIA but Does Not Contribute to Aberrant Cytokine Production by Macrophages - Maemura, Tadashi; Kuroda, Makoto; Armbrust, Tammy; Yamayoshi, Seiya; Halfmann, Peter J.; Kawaoka, Yoshihiro (mBio, 2021)
Viruses infect cells mainly via specific receptors at the cell surface. Antibody-dependent enhancement (ADE) of infection is an alternative mechanism of infection for viruses to infect immune cells that is mediated by antibodies and IgG receptors (FcγRs). The coronavirus disease 2019 (COVID-19) pandemic has raised concerns about the detrimental effects of antibodies. Antibody-dependent enhancement (ADE) of infection is one of the biggest concerns in terms of not only the antibody reaction to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) upon reinfection with the virus but also the reaction to COVID-19 vaccines. In this study, we evaluated ADE of infection by using COVID-19 convalescent-phase plasma and BHK cells expressing human Fcγ receptors (FcγRs). We found that FcγRIIA and FcγRIIIA mediated modest ADE of infection against SARS-CoV-2. Although ADE of infection was observed in monocyte-derived macrophages infected with SARS-CoV-2, including its variants, proinflammatory cytokine/chemokine expression was not upregulated in macrophages. SARS-CoV-2 infection thus produces antibodies that elicit ADE of infection, but these antibodies do not contribute to excess cytokine production by macrophages. IMPORTANCE Viruses infect cells mainly via specific receptors at the cell surface. Antibody-dependent enhancement (ADE) of infection is an alternative mechanism of infection for viruses to infect immune cells that is mediated by antibodies and IgG receptors (FcγRs). Because ADE of infection contributes to the pathogenesis of some viruses, such as dengue virus and feline coronavirus, it is important to evaluate the precise mechanism of ADE and its contribution to the pathogenesis of SARS-CoV-2. Here, using convalescent-phase plasma from COVID-19 patients, we found that two types of FcγRs, FcγRIIA and FcγRIIIA, mediate ADE of SARS-CoV-2 infection. Although ADE of infection was observed for SARS-CoV-2 and its recent variants, proinflammatory cytokine production in monocyte-derived macrophages was not upregulated. These observations suggest that SARS-CoV-2 infection produces antibodies that elicit ADE of infection, but these antibodies may not be involved in aberrant cytokine release by macrophages during SARS-CoV-2 infection.